2021
DOI: 10.1111/sltb.12772
|View full text |Cite
|
Sign up to set email alerts
|

Parental suicide attempt and subsequent risk of pre‐enlistment suicide attempt among male and female new soldiers in the U.S. Army

Abstract: Objective: Suicide and suicide attempts among U.S. Army soldiers are a significant concern for public health. This study examined the association of parental suicide attempt prior to age 13 of the soldier with subsequent risk of pre-enlistment suicide attempt. Method: We conducted secondary analyses of survey data from new soldiers who participated in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) (N = 38,396). A series of logistic regression analyses were conducted. Results: Of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recent work from our group has shown that parental history of SA is associated with increased risk of pre-enlistment SA among new soldiers in the US Army (Wang et al, 2021). Twin and other genetically informative studies suggest that SA is moderately (17%) heritable (Fu et al, 2002), and that parental psychiatric illness explains almost half of the genetic transmission of SA (Kendler, Ohlsson, Sundquist, Sundquist, & Edwards, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Recent work from our group has shown that parental history of SA is associated with increased risk of pre-enlistment SA among new soldiers in the US Army (Wang et al, 2021). Twin and other genetically informative studies suggest that SA is moderately (17%) heritable (Fu et al, 2002), and that parental psychiatric illness explains almost half of the genetic transmission of SA (Kendler, Ohlsson, Sundquist, Sundquist, & Edwards, 2020).…”
Section: Discussionmentioning
confidence: 87%